2017
DOI: 10.1016/j.ehb.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Do boys eat better than girls in India? Longitudinal evidence on dietary diversity and food consumption disparities among children and adolescents

Abstract: This paper examines the dynamics of gender-based disparities in the intra-household allocation of food during childhood and adolescence in Andhra Pradesh and Telangana by using three rounds of longitudinal data from two cohorts. While boys are advantaged at all ages (except for the Younger Cohort at 12 years old), the pro-boy gap widens markedly at 15 years old. Specifically, mid-adolescent girls tend to consume fewer protein- and vitamin-rich foods such as eggs, legumes, root vegetables and fruit. This result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 38 publications
9
90
4
Order By: Relevance
“…Another explanation, which was not mentioned by any of these studies and can only be shown by including individual dietary intakes, may relate to pro‐male food allocation processes in which girls are allocated fewer micronutrient‐rich foods than boys. Data from the Young Lives cohort point toward such a pro‐boy gap, showing how “disparities between mid‐adolescent boys and girls are driven by the increased likelihood of boys to consume protein‐ and vitamin‐rich foods” (p. 109) …”
Section: Discussionmentioning
confidence: 99%
“…Another explanation, which was not mentioned by any of these studies and can only be shown by including individual dietary intakes, may relate to pro‐male food allocation processes in which girls are allocated fewer micronutrient‐rich foods than boys. Data from the Young Lives cohort point toward such a pro‐boy gap, showing how “disparities between mid‐adolescent boys and girls are driven by the increased likelihood of boys to consume protein‐ and vitamin‐rich foods” (p. 109) …”
Section: Discussionmentioning
confidence: 99%
“…vi Aurino (2016) using the same dataset as this paper (but without the fourth round when children were 19)…”
Section: Household Characteristicsmentioning
confidence: 99%
“…Longitudinal data in a survey from India show that dietary diversity is lower in girls than boys at most ages, and the female disadvantage is largest in adolescence [14]. A review of 63 studies on macronutrient intake in adolescent girls found that ­global protein intake was adequate (mean ± SD = 58 ± 17 g/day), except among older adolescents living in Africa (mean ± SD = 39 ± 3 g/day) [15].…”
Section: Nutritional Requirements and Dietmentioning
confidence: 99%